Clinicopathologic Characteristics and Outcomes for Patients With KRAS G12D-Mutant NSCLC - Alissa J. Cooper, MD; Alona Muzikansky, MA; Jochen Lennerz, MD, PhD; Farhaana Narinesingh, M.B.B.S.; Mari Mino-Kenudson, MD; Yin P. Hung, MD, PhD; Zofia Piotrowska, MD, MHS; Ibiayi Dagogo-Jack, MD; Lecia V. Sequist, MD, MPH; Justin F. Gainor, MD; Jessica J. Lin, MD; Rebecca S. Heist, MD, MPH (JTO Clinical and Research Reports, 2022)
Introduction: Co-occurring mutations in KRAS-mutant NSCLC are associated with discrete biological properties and modulate therapeutic susceptibilities. As G12D-specific inhibitors are expected to enter the clinic, we sought to investigate the characteristics and outcomes of patients with KRAS G12D-mutant NSCLC. Methods: This was a retrospective single-institution study. Patients with NSCLC and KRAS G12D mutations detected by the Massachusetts General Hospital SNaPshot next-generation sequencing assay were identified. Clinical and pathologic characteristics were collected by chart review. Results: A total of 107 patients with KRAS G12D-mutant NSCLC were identified. Most patients were former smokers (80, 74.8%) and had tumors with adenocarcinoma pathologic subtype (93, 86.9%). Among 56 patients evaluated for programmed death-ligand 1 expression, tumor proportion score was less than 50% in 43 (76.8%). Concomitant mutations were identified in STK11 (17 of 107, 15.9%), KEAP1 (10 of 58, 17.2%), TP53 (36 of 107, 33.6%), and SMARCA4 (11 of 107, 10.3%). Among 57 patients treated with first-line therapy, patients with STK11 co-mutations had shorter progression-free survival (1.2 mo, 95% confidence interval [CI]: 0.6–2.9 versus 4.1 mo, 95% CI: 2.5–6.0, p = 0.0235) and overall survival (4.3 mo, 95% CI: 1.2–10.6 versus 17.9 mo, 95% CI: 8.6–31.1, p = 0.0018) compared with wild type. Patients with KEAP1 co-mutations had shorter overall survival (4.6 mo, 95% CI: 1.2–10.6 versus 17.9 mo, 95% CI: 7.1–30.1, p = 0.0125) than those without. TP53 co-mutations exerted no influence on survival. Conclusions: Co-occurring mutations were common in patients with KRAS G12D-mutant NSCLC. STK11 and KEAP1 co-mutations were associated with worse clinical outcomes, whereas co-occurring TP53 did not affect survival.